Regional Features of the Serotype Composition of Streptococcus pneumoniae isolated from Bacterial Carriers of Preschool Age in the Republic of Tatarstan - G. G. Isaeva; L. T. Bayazitova; A. Z. Zaripova; O. F. Tupkina; T. A. Chazova; R. M. Khusainova; Yu. A. Tyurin; V. B. Ziatdinov (Эпидемиология и вакцинопрофилактика)
Relevance. Vaccination of the child population against pneumococcal infection (PI) has been carried out in the Republic of Tatarstan according to the national calendar of preventive vaccinations since 2014. The vaccination scheme includes vaccination with PCV-13 conjugated pneumococcal vaccine.Aim. Study of the the frequency of bacterial transmission and the serotype landscape of S. pneumoniae isolated from healthy children- bacterial carriers of preschool age in the Republic of Tatarstan (RT).Materials and methods. During the period from 2016 to 2022, 1,426 children from Kazan and the districts of the Republic of Tatarstan were examined. Examination of nasopharyngeal smears was carried out by the classical bacteriological method. Serotyping was performed using molecular genetic methods (PCR).Results. The detection rate of S. pneumoniae among healthy preschool children varied in different years from 29.5 to 63%, averaging 38.5%. In urban children, the incidence of pneumococcal transmission was significantly higher than in rural children (p<0.01). Also, when analyzing the serotype landscape, mixed colonization by several serotypes was observed. As of January 1, 2021, the immune layer to the pathogen PI among preschool children was 81.7%. Monitoring of the serotype landscape of S.pneumoniae strains circulating in the RT showed the dominance of vaccine serotypes (67.2%), of which 44.4% are PCV13 serotypes. The proportion of non–vaccinated serotypes is 26%, untyped - 6.8%. Unvaccinated serotypes 35B (21.3%) and 23A (13.6%) dominated in vaccinated children, as well as serotypes not included in the PKV-13 vaccine cocktail, but included in the PPSV-23 polysaccharide vaccine not used for vaccination of children, namely 11AD (15.3%) 9LN (9.6%). In unvaccinated children, on the contrary, vaccine serotypes included in PCV-13 prevailed: 6ABCD (17.3%), 19F (20.9%), and unvaccinated serotypes 11AD, 9LN, 35B, 23A were detected with lower frequency 11,8%, 10,0%, 4,2%, 7,3% accordingly.Conclusion. Data on the regional features of the pneumococcal serotype landscape can be the basis for expanding the vaccine cocktail due to the dominant serotypes: 9LN,11 AD, 35B, 23A.